Analisis hubungan self esteem dengan impulsive buying pada mahasiswa - Indrayani, Indrayani; Hardaningrum, Tri Wahyu; Nurjannah, Eka (Journal of Management and Digital Business, 2024)
The purpose of this study is to determine the effect of self-esteem on impulse buying behavior among students at Balikpapan University. Shopping has become an activity that involves psychological needs, lifestyle, and pleasure. Social, economic, and cultural elements influence consumer behavior, including in the context of impulsive shopping. This research highlights the connection between self-esteem and impulsive shopping behavior among university students at Balikpapan University by finding a significant negative connection between the two variables. Individuals with low self-esteem tend to be more prone to impulsive shopping behavior as compensation to improve their self-esteem. The results also show that individuals with high self-esteem tend to keep their shopping behavior under control. In the face of social and cultural pressures influencing consumer behavior, a comprehensive and collaborative approach is crucial to building effective marketing strategies and consumer interventions. With a deeper understanding of the psychological elements that influence consumer behavior, companies can develop more adaptive and relevant strategies to meet the needs and drive consumer preferences in this modern era.